The Gospel according to Star wars : faith, hope, and the force - McDowell, John C. (Louisville, Ky. : Westminster John Knox Press, 2007)
"Star Wars is one of the most beloved movie series of all time, and in this book John McDowell explores the many spiritual themes that weave throughout the six films. From the Force to the dark side, the issues discussed in the films have a moral and spiritual complexity that, if paid attention to, can help us better understand our place in the world and our relation to others and to God. George Lucas, the creator of Star Wars, did not intend for his films to be mere entertainment, McDowell argues. Rather, he hoped his films would be used as a vehicle for moral education."--Publisher's website.
A new myth: the truthfulness of Star wars -- The force of the divine: God and the good -- Evil strikes back -- Beware the dark side within: the tragedy of Anakin Skywalker -- The politics of evil -- Rebelling against evil: the violence of Star wars -- Feeling the force: the ethics of the good life -- A new hope: redemption in Star wars.
Includes bibliographical references (p. 172-191) and index.
Keywords: Star Wars films; Motion pictures -- Religious aspects -- Christianity